2019
DOI: 10.1164/rccm.201810-1891oc
|View full text |Cite
|
Sign up to set email alerts
|

Resequencing Study Confirms That Host Defense and Cell Senescence Gene Variants Contribute to the Risk of Idiopathic Pulmonary Fibrosis

Abstract: Rationale: Several common and rare genetic variants have been associated with idiopathic pulmonary fibrosis, a progressive fibrotic condition that is localized to the lung. Objectives: To develop an integrated understanding of the rare and common variants located in multiple loci that have been reported to contribute to the risk of disease. Methods: We performed deep targeted resequencing (3.69 Mb of DNA) in cases (n = 3,624) and control subjects (n = 4,442) across genes and regions previously associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 28 publications
(33 reference statements)
3
68
1
Order By: Relevance
“…Indeed, in about 20% of familial IPF cases, mutations have been found in genes involved in telomere function (TERT and TERC) and protein folding and secretion that impact the function of epithelial cells (14)(15)(16). Furthermore, disease-associated gene variants defined in genome-wide screens have been linked to defects in host defense and regulation of cellular senescence (2,17).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in about 20% of familial IPF cases, mutations have been found in genes involved in telomere function (TERT and TERC) and protein folding and secretion that impact the function of epithelial cells (14)(15)(16). Furthermore, disease-associated gene variants defined in genome-wide screens have been linked to defects in host defense and regulation of cellular senescence (2,17).…”
Section: Introductionmentioning
confidence: 99%
“…It has become clear through the past two decades that pulmonary fibrosis is a heritable syndrome, and studies of FIP have yielded new insights into the pathobiology of ILD with broad relevance. With increasing evidence indicating that known genetic risk factors for sporadic and familial ILD are much more similar than different, 35,[118][119][120] considerations that inform the approach to and care of patients and families with FIP are likely to become increasingly relevant to broad groups of patients with ILD and their families.…”
Section: Resultsmentioning
confidence: 99%
“…Family-based cohort studies have focused primarily on rare genetic variants of large effect in families; however, common genetic variation also contributes to FIP risk. [118][119][120] The available data suggest that common genetic variants linked to IPF risk by linkage 118 or genome-wide association studies, 119 including the MUC5B promoter polymorphism and more than 15 additional loci 119,[121][122][123] have similar effect sizes in familial and sporadic IPF patients. 119,120 As common genetic variants follow complex rather than Mendelian inheritance patterns, genetic testing for common genetic variants does not currently have a role in the clinical evaluation or care of patients with FIP.…”
Section: Pulmonary Fibrosis Associated With Other Systemic Disordersmentioning
confidence: 99%
“…Importantly, this study not only identified risk variants, but also drew connections between specific variants (rs5743890) in TOLLIP and differential mortality from disease [21]. However, a recent study suggested that rs5743890 in TOLLIP was not associated with increased risk of IPF when adjusted for the presence of other genetic risk factors such as MUC5B [38].…”
Section: Muc5bmentioning
confidence: 89%
“…Very recently, a combined analysis of rare and common variants of 1510 patients with IPF showed 1046 patients (69.2%) were carriers of the rs35705950 (MUC5B) risk allele, but only 30 (3%) of them were also carriers of a rare variant within TERT, whereas 34 (7%) of the non-carriers of rs35705950 were also carriers of a rare variant within TERT [42]. Furthermore, in a recently reported study of 3624 IPF patients and 4442 controls, deep targeted resequencing of candidate genes showed that TERT and RTEL1 were independently associated with the risk of IPF [38].…”
Section: Combined Rare and Common Variantsmentioning
confidence: 99%